2012
DOI: 10.1182/blood-2012-04-403733
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitors in multiple myeloma: 10 years later

Abstract: Proteasome inhibition has emerged as an important therapeutic strategy in multiple myeloma (MM). Since the publication of the first phase 1 trials of bortezomib 10 years ago, this first-in-class proteasome inhibitor (PI) has contributed substantially to the observed improvement in survival in MM patients over the past decade. Although first approved as a single agent in the relapsed setting, bortezomib is now predominantly used in combination regimens. Furthermore, the standard twice-weekly schedule may be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
373
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 449 publications
(381 citation statements)
references
References 77 publications
(91 reference statements)
4
373
0
4
Order By: Relevance
“…This indicates that the proteasome inhibitors investigated are not activators of PXR, which usually mediates the induction of genes, including ABCB1, ABCC2 and ABCG2 (32)(33)(34). This is concordant with previous in vitro studies that reported no significant changes in the expression of certain drug transporter genes (ABCB1, ABCC1 and ABCG2), even following long-term exposure to bortezomib (35) or an increase in ABCB1 expression following six months of treatment with increasing concentrations of carfilzomib only (36).…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that the proteasome inhibitors investigated are not activators of PXR, which usually mediates the induction of genes, including ABCB1, ABCC2 and ABCG2 (32)(33)(34). This is concordant with previous in vitro studies that reported no significant changes in the expression of certain drug transporter genes (ABCB1, ABCC1 and ABCG2), even following long-term exposure to bortezomib (35) or an increase in ABCB1 expression following six months of treatment with increasing concentrations of carfilzomib only (36).…”
Section: Discussionsupporting
confidence: 80%
“…1,2 An enzymatically active proteasome is composed of a 20S core and at least one proteasomal activator complex. 3 The 20S is the catalytic core that is activated through association with proteasomal activators.…”
mentioning
confidence: 99%
“…For example, combination with lenalidomide or thalidomide may improve clinical benefit as these agents alter cytokine production and enhance T-and NK-cellmediated immune responses [52,53]. In addition, as proteasome inhibition stimulates apoptosis, reduces angiogenesis, cytokine signaling and cell adhesion, and can increase the susceptibility of multiple myeloma cells to NK cell-mediated killing [54,55], combination with bortezomib may also be effective [56,57]. In preclinical studies, overnight pretreatment of multiple myeloma cells with antibodies enhanced the efficacy of the ADCC-mediating mAb trastuzumab [62].…”
Section: Elotuzumab-based Combination Therapy Preclinical Rationalementioning
confidence: 99%